Genome-wide transcriptome analysis of Echinococcus multilocularis larvae and germinative cell cultures reveals genes involved in parasite stem cell function - Herz, Michaela; Zarowiecki, Magdalena; Wessels, Leonie; Pätzel, Katharina; Herrmann, Ruth; Braun, Christiane; Holroyd, Nancy; Huckvale, Thomas; Bergmann, Monika; Spiliotis, Markus; Koziol, Uriel; Berriman, Matthew; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The lethal zoonosis alveolar echinococcosis is caused by tumour-like growth of the metacestode stage of the tapeworm Echinococcus multilocularis within host organs. We previously demonstrated that metacestode proliferation is exclusively driven by somatic stem cells (germinative cells), which are the only mitotically active parasite cells that give rise to all differentiated cell types. The Echinococcus gene repertoire required for germinative cell maintenance and differentiation has not been characterised so far. We herein carried out Illumina sequencing on cDNA from Echinococcus metacestode vesicles, from metacestode tissue depleted of germinative cells, and from Echinococcus primary cell cultures. We identified a set of ~1,180 genes associated with germinative cells, which contained numerous known stem cell markers alongside genes involved in replication, cell cycle regulation, mitosis, meiosis, epigenetic modification, and nucleotide metabolism. Interestingly, we also identified 44 stem cell associated transcription factors that are likely involved in regulating germinative cell differentiation and/or pluripotency. By in situ hybridization and pulse-chase experiments, we also found a new general Echinococcus stem cell marker, EmCIP2Ah, and we provide evidence implying the presence of a slow cycling stem cell sub-population expressing the extracellular matrix factor Emkal1. RNA-Seq analyses on primary cell cultures revealed that metacestode-derived Echinococcus stem cells display an expanded differentiation capability and do not only form differentiated cell types of the metacestode, but also cells expressing genes specific for protoscoleces, adult worms, and oncospheres, including an ortholog of the schistosome praziquantel target, EmTRPMPZQ. Finally, we show that primary cell cultures contain a cell population expressing an ortholog of the tumour necrosis factor α receptor family and that mammalian TNFα accelerates the development of metacestode vesicles from germinative cells. Taken together, our analyses provide a robust and comprehensive characterization of the Echinococcus germinative cell transcriptome, demonstrate expanded differentiation capability of metacestode derived stem cells, and underscore the potential of primary germinative cell cultures to investigate developmental processes of the parasite. These data are relevant for studies into the role of Echinococcus stem cells in parasite development and will facilitate the design of anti-parasitic drugs that specifically act on the parasite germinative cell compartment.